Caseinolytic Specificity of Cardosin, an Aspartic Protease from the Cardoon Cynara cardunculus L.: Action on Bovine αs- and β-Casein and Comparison with Chymosin - Macedo, I. Queiroz (1996)
The action of cardosin on bovine αs- and β-casein at 30 °C in 50 mM citrate buffer (pH 6.2) was studied. Peptides were isolated by reversed-phase HPLC on C18 columns and identified from their amino acid composition and N-terminal amino acid sequence. The relative susceptibility of peptide bonds cleaved was Phe23-Phe24 > Trp164-Tyr165 > Tyr166-Val167 > Tyr165-Tyr166 > Phe153-Tyr154 > Phe145-Tyr146 ≈ Leu149-Phe150 ≈ Leu156-Asp157 ≈ Ala163-Trp164 for αs1-casein and Leu192-Tyr193 > Leu191-Leu192 ≈ Leu165-Ser166 > Phe190-Leu191 ≥ Ala189-Phe190 ≈ Leu127-Thr128 for β-casein. In αs2-casein, cardosin cleaved the bonds Phe88-Tyr89 and Tyr95-Leu96. The enzyme shows a clear preference for bonds between hydrophobic, bulky amino acids, cleaving four consecutive peptide bonds in extremely bulky, hydrophobic regions of both αs1-CN (Ala163-Val167) and β-CN (Ala189-Tyr193), which was less attacked by chymosin in various experimental conditions. The active site cleft of cardosin accommodates sequences as bulky as Trp-Tyr-Tyr in different subsites (S1 to S‘2, S2 to S‘1, and probably S3 to S1). Several bitter peptides were identified in the digests.